The Evolution of the relationship between education and economics: a bibliometric analysis - Shakenova, G.А.; Svyatov, S.A.; Abilov, D.K.; Nevmatulina, K.A.; Khishauyeva, Zh.Т. (BUKETOV BUSINESS REVIEW, 2024)
Object: To analyze the evolution of the links between education and the economy, which is important in the de velopment of each country, widely discussed in the economic literature Methods: For the analysis, the publications of researchers from the Scopus database were used. The analysis was carried out using VOSviewer software for visualization of bibiometric systems. The subject of scientific interest were publications in which the keywords "education" and economics are found. Results: The evolution of the transformation of the concepts selected for analysis is specified, under the influence of modern aspects, at different stages, including the period of formation. An analysis of historical changes previously showed basic concept is human capital, and modern aspects are investments, qualifications, profitability. It is noted that subsequent research has moved into the field of digitalization. Conclusions: As a result of the analysis, it was found that education is the main factor in increasing economic growth. In accordance with modern requirements, it determines the need to provide the workforce with the necessary skills and knowledge to achieve high success.